2019
DOI: 10.1186/s13256-019-2277-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous disappearance and recurrence of impending macular hole: a case report

Abstract: BackgroundThere have been several reports of spontaneous closure and reopening of a macular hole, however, in most of those cases, it was observed in eyes post vitrectomy. Here, we report a case of multiple episodes of spontaneous disappearance and recurrence of impending macular hole (stage 1B macular hole) with no history of previous surgery.Case presentationA 76-year-old Japanese man presented with a primary complaint of reduced visual acuity in his right eye. On initial examination, the visual acuity in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…3,10 Some authors have postulated that there may be ongoing vitreous traction or traction secondary to progressive glial proliferation; others have hypothesized that serine proteases may play a role. 3,8,9 In the current case, a posterior vitreous detachment was present at the time of the initial presentation, which was visualized clinically with a Weiss ring and on OCT with a detached posterior hyaloid overlying the macular hole, and therefore it is less likely that ongoing vitreous traction caused the recurrent opening. However, previous reports have demonstrated residual vitreous remnants by scanning electron microscopy in cases of posterior vitreous detachments that could serve as a source of ongoing traction.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…3,10 Some authors have postulated that there may be ongoing vitreous traction or traction secondary to progressive glial proliferation; others have hypothesized that serine proteases may play a role. 3,8,9 In the current case, a posterior vitreous detachment was present at the time of the initial presentation, which was visualized clinically with a Weiss ring and on OCT with a detached posterior hyaloid overlying the macular hole, and therefore it is less likely that ongoing vitreous traction caused the recurrent opening. However, previous reports have demonstrated residual vitreous remnants by scanning electron microscopy in cases of posterior vitreous detachments that could serve as a source of ongoing traction.…”
Section: Discussionmentioning
confidence: 65%
“…The first case reported by Golan and Barak 8 in 2015 demonstrated three episodes of opening and spontaneous closure of a full-thickness macular hole in a pseudophakic patient with history of myopia. The second report published in 2019 by Miyamoto et al 9 described a case of a recurrent outer retinal hole (stage 1B) with two episodes of spontaneous closure in an emmetropic patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are case reports of spontaneous closure with the resolution of inflammation and release of vitreous traction, patients may require surgical intervention. 6 , 7 , 8 Outcomes data from a retrospective review of patients with macular holes secondary to Behçet's disease in 2011 demonstrated poor closure rates (1/6 eyes) and no improvement in vision with surgical intervention; however, more recent data suggests a role for surgery. 9 Callaway et al published a multicenter case series of 16 eyes in 15 patients that underwent pars plana vitrectomy with indocyanine green dye assisted internal limiting membrane peel for macular hole secondary to various inflammatory etiologies.…”
Section: Discussionmentioning
confidence: 99%